First-generation immigrants feel socially excluded and have greater pro-violence attitudes than the native population in England and Wales. Issue 1 (11th January 2016) - Bui, Laura; Farrington, David P
Abstract : Purpose: – Studies examining immigrant generational status and violence have supported differences in the prevalence of violence between these groups. The purpose of this paper is to measure relevant risk factors for violence to focus on whether negative perceptions may contribute to understanding the between-generations differences in violence. Based on the literature, it is theorised that pro-violence attitudes would be related to and be higher in second-generation immigrants than first-generation immigrants, and that negative perceptions would mediate the relationship between pro-violence attitudes and violence. Design/methodology/approach: – Data to answer the study's key questions were taken from the 2010-2011 UK citizenship survey, where only the main sample was analysed. Findings: – The findings reveal that first-generation immigrants have a higher prevalence of pro-violence attitudes than the native population. Originality/value: – This suggests that there is an intergenerational transmission in violent attitudes, and this is a risk factor for actual violence in second-generation immigrants.